2013
DOI: 10.1007/s00228-013-1597-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and physician-related risk factors for hyperkalaemia in potassium-increasing drug–drug interactions

Abstract: PURPOSE: Hyperkalaemia due to potassium-increasing drug-drug interactions (DDIs) is a clinically important adverse drug event. The purpose of this study was to identify patient-and physicianrelated risk factors for the development of hyperkalaemia. METHODS: The risk for adult patients hospitalised in the University Hospital Zurich between 1 December 2009 and 31 December 2011 of developing hyperkalaemia was correlated with patient characteristics, number, type and duration of potassiumincreasing DDIs and freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Clinical trials, case reports, and laboratory studies show that co-trimoxazole induced hyperkalemia can occur quickly and can cause life threatening arrhythmias, especially among patients receiving angiotensin converting enzyme inhibitors or angiotensin receptor blockers. 13 15 16 19 33 34 Our previous research on this drug interaction showed a nearly sevenfold increased risk of hospital admission with hyperkalemia following co-trimoxazole treatment but no such risk with the same alternative antibiotics studied here. 14 In the analysis presented here, we found no increased risk of sudden death with nitrofurantoin or norfloxacin.…”
Section: Discussionmentioning
confidence: 51%
“…Clinical trials, case reports, and laboratory studies show that co-trimoxazole induced hyperkalemia can occur quickly and can cause life threatening arrhythmias, especially among patients receiving angiotensin converting enzyme inhibitors or angiotensin receptor blockers. 13 15 16 19 33 34 Our previous research on this drug interaction showed a nearly sevenfold increased risk of hospital admission with hyperkalemia following co-trimoxazole treatment but no such risk with the same alternative antibiotics studied here. 14 In the analysis presented here, we found no increased risk of sudden death with nitrofurantoin or norfloxacin.…”
Section: Discussionmentioning
confidence: 51%
“…The risk of death after 2 days from the detection of hyperkalemia was 5.3 times greater than in patients who were not exposed to PDDI, which led to this adverse event [34]. The combination, therefore, must be carefully evaluated with regard to the risk and benefit for each patient.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to PSHC, some other factors might also contribute to the occurrence of hyperkalemia in the 2 patients, such as the application of calcineurin inhibitors, glucocorticoids, and diuretics. [ 26 28 ] In this report, both of the cases received tacrolimus (calcineurin inhibitor) and prednisolone (a type of glucocorticoid) in immunosuppressive treatment that might increase the risk of hyperkalemia. Furthermore, blood transfusion might also stand for a potential risk factor for hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that when coprescribing medicine, it would be better to avoid using potassium-bearing citrate that may interfere with potassium homeostasis among patients with renal dysfunction. [ 26 , 32 ] If not, oral dose should be reduced according to the severity of renal dysfunction. In a previous study, sodium bicarbonate did not allow additional potassium into blood, and showed an effect equivalent to potassium-bearing citrate in the treatment of urinary stone, suggesting that sodium bicarbonate might be a better choice for patients who could not tolerate PC.…”
Section: Discussionmentioning
confidence: 99%